Pengaruh E-Modul Interaktif Terhadap Motivasi Dan Hasil Belajar Siswa Pada Pembelajaran AC Split: The Effect Of Interactive E-Modules On Student Motivation And Learning Outcomes In Split AC Lessons - I Made Hendra Wiratama; Kadek Rihendra Dantes; Jhony Langgeng Baruna Wirawan (Universitas Pendidikan Ganesha, 2026)
This study aimed to analyze the effect of using interactive e-module-based learning media on students' motivation and learning outcomes in Air Conditioner Split learning among Grade XI Electronics Engineering students at SMK Negeri 3 Singaraja. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 28 students selected through a saturated sampling technique. Data were collected through a learning motivation questionnaire and learning achievement tests that had met the requirements of validity and reliability. The data were analyzed using learning outcome improvement analysis and non-parametric statistical tests to determine the differences between the results before and after the treatment. The results showed that the use of interactive e-modules was able to improve students' learning motivation, reaching 95 percent, which was categorized as very high. The average student learning outcome score also increased from 59.82 in the pretest to 86.07 in the posttest, with the level of improvement categorized as moderate. Furthermore, the statistical test results indicated a significant difference between students' learning outcomes before and after the implementation of the interactive e-module. Therefore, it can be concluded that interactive e-module-based learning media have a positive and significant effect on students' motivation and learning outcomes in Air Conditioner Split learning at SMK Negeri 3 Singaraja. Keywords : interactive e-module, learning motivation, learning outcomes, air conditioner split.